Risk Management of Construction Enterprises – theoretical approach - Aneta Madyda (Communications of International Proceedings, 2023)
The present article is devoted to the process of risk management for construction enterprises in Poland. The key problem for entrepreneurs is to determine the existence of risk, its scale and influence on the organisation of an enterprise, as well as a possible reaction to it. Polish construction industry is closely connected with the overall economic situation. The macroeconomic risk, together with the pace of the development of Polish economy, has a strong influence on the level of demand for building services. The inclination towards undertaking construction ventures is bound up with the raise of GDP, as well as with the perception of the situation on the market and the prospect of development. This study is theoretical in its character. The article focuses on the elements the risk management process: identification, analysis and response to risk in construction projects against the background of the macroeconomic situation in Poland.
Keywords: risk; management; construction; project